2009
DOI: 10.1530/eje-08-0600
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of secondary adrenal insufficiency in patients with hypothalamic–pituitary disease: comparison between serum and salivary cortisol during the high-dose short synacthen test

Abstract: Objective: Accurate assessment of adrenal function is essential in patients with hypothalamicpituitary-adrenal (HPA) disease. The measurement of salivary cortisol (SaC) instead of serum cortisol (SeC) offers several advantages, such as the determination of the free hormone. We evaluated the diagnostic value of SeC and SaC both unstimulated and during a high-dose short synacthen test (HDT) in comparison to the insulin tolerance test (ITT). Design: Comparative study between 2005 and 2007. Methods: Fifty-five pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 44 publications
5
38
0
2
Order By: Relevance
“…According to the results of the preoperative ITTs which were performed on 55 patients in this study, we found that patients with basal serum cortisol levels between 165 and 496 nmol/l (6-18 mg/dl) required dynamic testing. The majority of previous studies determined the lower cut-off for basal cortisol as 100-110 nmol/l (3.6-4 mg/dl), but the upper cut-off was found to range between 300 and 494 nmol/l (10.8-17.9 mg/dl) (15)(16)(17)(18). In a metaanalysis of 12 studies, basal cortisol levels !5 mg/dl (138 nmol/l) were found to predict HPA insufficiency best, and values O13 mg/dl (365 nmol/l) predicted normal HPA function (19).…”
Section: Discussionmentioning
confidence: 96%
“…According to the results of the preoperative ITTs which were performed on 55 patients in this study, we found that patients with basal serum cortisol levels between 165 and 496 nmol/l (6-18 mg/dl) required dynamic testing. The majority of previous studies determined the lower cut-off for basal cortisol as 100-110 nmol/l (3.6-4 mg/dl), but the upper cut-off was found to range between 300 and 494 nmol/l (10.8-17.9 mg/dl) (15)(16)(17)(18). In a metaanalysis of 12 studies, basal cortisol levels !5 mg/dl (138 nmol/l) were found to predict HPA insufficiency best, and values O13 mg/dl (365 nmol/l) predicted normal HPA function (19).…”
Section: Discussionmentioning
confidence: 96%
“…A number of studies have quantified that cortisol in saliva reflects serum levels with good precision and is advocating salivary cortisol as an even better alternative to assess dynamic HPA axis activity. 15,[19][20][21][22] Early morning samples of free cortisol in saliva obtained with strict reference to the time of awakening and measured repeatedly, have shown good intra-individual stability. 23 The salivary cortisol levels, in this study, has reflected serum cortisol levels in most patients, showing very good correlation similar to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…23 The salivary cortisol levels, in this study, has reflected serum cortisol levels in most patients, showing very good correlation similar to other studies. 19,20,23 This implies that salivary cortisol can be an alternative diagnostic tool to assess severity of periodontitis, especially in patients with coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…SHT and SHG had a signi cant e ect on the post-ACTH levels, with SHT corresponding to a 77 nmol/L drop in peak Fatigue (16) glucocorticoid withdrawal (10) Pituitary tumour + radiation therapy (4) Non -pituitary sellar growth (6) Non-pituitary sellar growth + radiation therapy (6) Idiopathic pituitary insu ciency (5) Hypotension (2) Vomiting (1) Cranial radiation (1) ere was no correlation between either condition and morning serum cortisol levels.…”
Section: Risk Of Hpa Insu Ciency In Patients With Other Pituitary Hormentioning
confidence: 99%
“…ese studies have generally focused on speci c patient populations of pre- [6,7] and post-pituitary surgeries [8,9] and consequently proposed variable lower and upper serum basal cortisol levels that would obviate the need for patients to undergo further dynamic testing. [8,[10][11][12][13]. e primary purpose of this study was twofold: a) to assess the association between morning basal serum cortisol and serum cortisol levels a er dynamic test using a standard dose (250 μg) ACTH stimulation test; and, b) to determine upper and lower cuto values of morning basal cortisol that would obviate the need for dynamic testing in an outpatient setting.…”
mentioning
confidence: 99%